Pemanfaatan Serbuk Sabut Kelapa Sebagai Bahan Alternatif Pembuatan Kampas Rem Non-Asbestos Pada Sepeda Motor - Alfarisy, Abdul Aris Alfarisy; Burhanudin, Aan; Ma'mun, Hisyam (Badan Kerja Sama Teknik Mesin Indonesia, 2025)
This study is an experimental study in the manufacture of composite materials with coconut fiber powder reinforcement from coconut waste and aluminum powder from industrial waste. From this study, the characteristics of composite materials will be obtained with variations in the composition of coconut fiber powder and aluminum powder as reinforcement with a polyester resin matrix. This study is considered necessary to find composite materials that are not only superior in mechanical properties, but also optimal and utilize waste materials in large quantities that require proper management so as not to cause problems. The manufacture of this composite material uses coconut fiber powder, aluminum powder and polyester resin with a volume ratio of 30% coconut fiber powder, 30% aluminum powder, 40% resin, 40% coconut fiber powder, 20% aluminum powder, 40% resin, 45% coconut fiber powder, 15% aluminum powder, 40% resin, 50% coconut fiber powder, 10% aluminum powder, 40% resin, 60% coconut fiber powder, 0% aluminum powder, 40% resin. The process of making this composite material uses a press method with a vertical force pressure of 2,500 kg with sintering at a temperature of 150oC for 30 minutes. The characterization carried out includes the hardness and wear of each material composition. The hardness value closest to the hardness value of the comparative brake pads is the KL45AL15 specimen with an average hardness value of 33.1 kg/mm² with a composition of 45% coconut fiber powder, 15% aluminum powder, and 40% resin. And in the results of the brake pad wear test, the wear value closest to the wear value of the comparative brake pads is the KL60AL0 specimen with a wear value of 0.00252. with a composition of 60% coconut fiber powder, 0% aluminum powder, and 40% resin.